Analisis Determinan Knowladge dan Level of Education Perbankan Syari’ah terhadap Interest in Saving Pada Bank Muamalat Medan - Siregar, Rahman Siddik; Nasution, Muhammad Lathief Ilhamy (Jurnal Informatika Ekonomi Bisnis, 2023)
This study will examine the effect of the Determinants of Islamic Banking Knowledge and Education Level on Interest in Saving at Bank Muamalat Medan Branch Office. The type of research used in this case is quantitative research. The data in this study are primary data in the form of questionnaires which have been distributed to 100 millennial workers. Sample The method used is purposive sampling technique. Hypothesis testing was carried out using SPSS 20.0 for windows by testing the independent variables, namely the Determinants of Knowledge and Level of Education and the dependent variable, namely Interest in Saving. The results of this study indicate that the determinants of knowledge and education level simultaneously have a significant effect on the intention to save. For the partial test, Determinant Knowledge has a positive and significant effect on Saving Interest. The level of education has a positive and significant effect on the interest in saving.